2005
DOI: 10.1007/s00268-005-7661-z
|View full text |Cite
|
Sign up to set email alerts
|

Giant Liver Hemangioma: Therapy by Enucleation or Liver Resection

Abstract: Hemangioma is the most common primary tumor of the liver. The widespread use of ultrasonography (USG) and computed tomography (CT) has made the diagnosis more common. Although the vast majority of hemangiomas are diagnosed incidentally and are asymptomatic, treatment is still controversial. Surgery is the treatment of choice, especially in giant, symptomatic hemangiomas and uncertainty of diagnosis. Twenty-two patients (median age: 46 years) underwent resection (n = 12) or enucleation (n = 10) for liver hemang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 29 publications
1
79
1
3
Order By: Relevance
“…4,[8][9][10][11][12] In the past decades non-surgical modalities have been investigated for the treatment of the disease, such as transcatheter arterial embolization and radiation therapy. However, only short-term control could be achieved for hepatic hemangiomas.…”
Section: Introductionmentioning
confidence: 99%
“…4,[8][9][10][11][12] In the past decades non-surgical modalities have been investigated for the treatment of the disease, such as transcatheter arterial embolization and radiation therapy. However, only short-term control could be achieved for hepatic hemangiomas.…”
Section: Introductionmentioning
confidence: 99%
“…Two common procedures for surgical intervention include enucleation and resection. Until recently, authors reported that enucleation was associated with decreased morbidity, intraoperative bleeding, hospital stay, and operative times [29][30][31][32]. Nevertheless, these studies included few patients with hemangiomas >10cm.…”
Section: Discussionmentioning
confidence: 99%
“…When surgery is indicated, hemangioma can be removed by both liver resection and enucleation procedures. The choice between liver resection and enucleation depends mainly on location, number and size tumor, complications, preference and technical skills of surgeon [33,34]. Enucleation is more preferred in peripheral and right-sided located hemangioma.…”
Section: Surgical Approachmentioning
confidence: 99%
“…Enucleation is more preferred in peripheral and right-sided located hemangioma. Also it is more suitable in case of multiple locations leading to preserve normal liver parenchyma [12,33,34]. Liver anatomic resection is more preferred in centrally located lesion or when lesion is near or compresses large vessels with high risk of bleeding and prolonged operative time [35][36][37].…”
Section: Surgical Approachmentioning
confidence: 99%
See 1 more Smart Citation